Mediation of market orientation on entrepreneurial orientation and firms’ performance: An empirical study on Indonesian SMEs - Santoso, Wiliam; Sunyoto, Hadi Kusuma; Shrinity, Parthasarathi; Gunawan, Clara Angelia (Universitas Mercu Buana, 2025)
SMEs have proven to be fundamental to economic growth, especially in an emerging economy like Indonesia. They also reduce the unemployment rate because 99% of the businesses are categorized as SMEs. However, there are common SME problems: their capabilities to operate efficiently. This research uses multiple linear regression analysis to uncover the influence of entrepreneurial orientation (EO) on firms’ performance of food and beverage SMEs in Surabaya. Survey questionnaires were disseminated to managers, CEOs, and business owners of food and beverage SMEs in Surabaya. Moreover, each EO dimension will also be tested to identify their significance on firm performance. Market orientation (MO) was also tested to seek its influence on firms' performance and its mediation impact on the relationship between entrepreneurial orientation and performance. The findings of this study were that overall EO positively influences MO and firms’ performance. Innovativeness, risk-taking, and autonomy of EO were significant to firms’ performance. However, the proactiveness and competitive aggressiveness of EO and MO were found not to have significance on firms’ performance. MO was also found not to mediate EO and firms’ performance.